Pengaruh Disiplin Kerja Dan Gaya Kepemimpinan Partisipatif Terhadap Kinerja Pegawai Pada UPBJJ-UT Palembang - Zein Ghozali; Munyati; Indah Mawarni; Tutik Pebrianti; Vivin Afini (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
The aim of this study is to test the effect of Discipline Of Work And Participative Leadership Style on the Employee Performance Of Distance Learning Program Unit of Universitas Terbuka Palembang (UPBJJ-UT Palembang). By using 2 independent variables, and Employee Performance as dependent variable. The use of independent variables based on Prijodarminto's theory (1994) and Husain (2011) and dependent variables based on Rao's theory (1992) The Study is conducted in UPBJJ-UT Palembang. The data used are primary data in the form of questionnaires to 61 respondents who are all employees of UPBJJ-UT Palembang. Multiple Regression analysis using SPSS for Windows Ver 22,0 is used to analyse the data. The results shows that, in partial test, Work Discipline and Style of Participatory Leadership have significant effect on Employee Performance. Furthermore, in simultaneous test, Work Discipline and Participatory Leadership Style are significantly affecting Employee Performance.